Multi-Mode Coupling Enabled Broadband Coverage for Terahertz Biosensing Applications - Dongyu Hu; Mengya Pan; Yanpeng Shi; Yifei Zhang (Biosensors)
Terahertz (THz) biosensing faces critical challenges in balancing high sensitivity and broadband spectral coverage, particularly under miniaturized device constraints. Conventional quasi-bound states in the continuum (QBIC) metasurfaces achieve high quality factor (Q) but suffer from narrow bandwidth, while angle-scanning strategies for broadband detection require complex large-angle illumination. Here, we propose a symmetry-engineered, all-dielectric metasurface that leverages multipolar interference coupling to overcome this limitation. By introducing angular perturbation, the metasurface transforms the original magnetic dipole (MD)-dominated QBIC resonance into hybridized, multipolar modes. It arises from the interference coupling between MD, toroidal dipole (TD), and magnetic quadrupole (MQ). This mechanism induces dual counter-directional, frequency-shifted, resonance branches within angular variations below 16°, achieving simultaneous 0.42 THz broadband coverage and high Q of 499. Furthermore, a derived analytical model based on Maxwell equations and mode coupling theory rigorously validates the linear relationship between frequency splitting interval and incident angle with the Relative Root Mean Square Error (RRMSE) of 1.4% and the coefficient of determination (<semantics>R2</semantics>) of 0.99. This work establishes a paradigm for miniaturized THz biosensors, advancing applications in practical molecular diagnostics and multi-analyte screening.